1991
DOI: 10.1530/acta.0.1250397
|View full text |Cite
|
Sign up to set email alerts
|

Production of a specific polyclonal antibody against the rat β thyroid receptor, using synthetic peptide as antigen

Abstract: Abstract. We have developed a polyclonal antibody to a synthetic peptide corresponding to the deduced amino acid residues 67–80 of the amino terminal sequence of the rat thyroid receptor β cDNA. Immunopositive sera were identifed by radioimmunoassay and purified by affinity chromatography. The antibody specifically immunoprecipitated the labelled thyroid receptor β synthetized in vitro but not the rat thyroid receptor α. Furthermore, 38% of the L-T3 binding capacity of the rat liver nuclear receptor were immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One peptide corresponding to residues 71–85 of the rat β1‐TR N terminal region and another to residues 12–23 of the N terminal region common to rat α1‐ and α2‐TR (α‐TR) were synthesized (IGBMC, Strasbourg‐Illkirch, France), checked by high‐performance liquid chromatography (HPLC) for purity (>95%), and coupled to keyhole limpet hemocyanin (KLH; Megathura crenulata ; Sigma‐Aldrich Chimie France), using m‐maleimidobenzoic acid N‐hydroxy‐succinimide ester as previously described (Puymirat et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…One peptide corresponding to residues 71–85 of the rat β1‐TR N terminal region and another to residues 12–23 of the N terminal region common to rat α1‐ and α2‐TR (α‐TR) were synthesized (IGBMC, Strasbourg‐Illkirch, France), checked by high‐performance liquid chromatography (HPLC) for purity (>95%), and coupled to keyhole limpet hemocyanin (KLH; Megathura crenulata ; Sigma‐Aldrich Chimie France), using m‐maleimidobenzoic acid N‐hydroxy‐succinimide ester as previously described (Puymirat et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation and characterization of the p l thyroid receptor antibodies has been described in previous work (Puymirat et al, 1991(Puymirat et al, ,1992a. Cultures were fixed with 1% paraformaldehyde in 0.1 M sodium phosphate buffer, 0.2% NaCl, pH 7.4 (PBS) for 15 min at room temperature.…”
Section: Immunocytochemical Localization Of Pl Thyroid Receptorsmentioning
confidence: 99%
“…Cultures were fixed with 1% paraformaldehyde in 0.1 M sodium phosphate buffer, 0.2% NaCl, pH 7.4 (PBS) for 15 min at room temperature. Cultures were then washed with PBS, permeabilized for 10 min with 0.2% Triton X-100, and incubated with affinity-purified anti-pl antibodies (10 pg/ml) for 2 h at room temperature (Puymirat et al, 1991). After washing with PBS, cells were incubated with an FITC goat anti-rabbit IgG (1150, obtained from Boehringer).…”
Section: Immunocytochemical Localization Of Pl Thyroid Receptorsmentioning
confidence: 99%
“…13 In the liver, THRs are expressed in hepatocytes, cholangiocytes, kupffer cells, and HSCs, and therefore, TH can influence almost all aspects of hepatic physiology. 14 17 Epidemiological studies have shown an increased incidence of MASLD with both overt and subclinical hypothyroidism in humans. 18 – 23 Furthermore, animal models of MASH have shown evidence of intra-hepatic TH insufficiency, suggesting deregulated TH metabolism in fatty liver.…”
Section: Nuclear Hormone Receptors and Mashmentioning
confidence: 99%